Synthesis and characterization of a biopolymer of glycerol and macadamia oil - Pires, Osmar Antonio Baldo [UNESP]; Alarcon, Rafael Turra [UNESP]; Gaglieri, Caroline [UNESP]; da Silva-Filho, Luiz Carlos [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2019)
The main objective of this work was the synthesis of a polymer using a vegetable and renewable feedstock and following the green chemistry principles. The use of macadamia oil (extracted from Macadamia integrifolia nuts) in a synthesis route was achieved under mild temperature and pressure conditions. The produced material was submitted to a series of characterization techniques. Thermal analysis was used to determine its thermal stability (140.0 °C), its degradation pattern with the involved kinetic, and its glass transition (midpoint at 48.8 °C). Infrared spectrometry found the general mechanism of polymerization of macadamia oil with pre-polymer (glycerol and maleic anhydride) and identified functional groups of the polymer. Some interesting characteristics of the macadamia polymer include good removal of organic dyes from aqueous solutions, which demonstrates the great interaction of its surface with organic molecules that leads to a potential application as an encapsulation material for substances of nutritional and pharmacological interests. This adsorption may be related to the polymer surface that is very rough as shown by scanning electron microscopy images. Another interesting phenomenon demonstrated was the macadamia polymer fluorescence that indicates potential applications in electronic devices.
Keywords: Glycerol; Infrared; Macadamia oil; Oil polymer; Thermal analysis; Ultraviolet spectroscopy